2018
DOI: 10.3892/ol.2018.9382
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reverses the resistance mechanism of lung adenocarcinoma cells that knocks down the Nrf2 gene

Abstract: The nuclear factor, er ythroid 2 like 2 (Nrf2)/antioxidant response element (ARE) pathway has an important role in the drug resistance of adenocarcinoma, and may act via different mechanisms, including the mitogen-activated protein kinase (MAPK) pathway. However, it has remained elusive whether metformin affects Nrf2 and regulates Nrf2/ARE in adenocarcinoma. In the present study, reverse-transcription quantitative polymerase chain reaction, cell transfection, western blot analysis, a Cell Counting kit-8 assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…Raf-ERK signaling attenuation was shown to be involved in the regulation of Nrf2 by metformin in the treatment of lung cancer (25). However, the p38 MAPK and JNK signaling pathways were not found to affect Nrf2 protein expression (21). Our study produced similar results.…”
Section: Non-decreased Nrf2 Expression In Patients After Neoadjuvant Chemotherapy Is Associated With Poor Survival and Chemoresistance Insupporting
confidence: 79%
See 1 more Smart Citation
“…Raf-ERK signaling attenuation was shown to be involved in the regulation of Nrf2 by metformin in the treatment of lung cancer (25). However, the p38 MAPK and JNK signaling pathways were not found to affect Nrf2 protein expression (21). Our study produced similar results.…”
Section: Non-decreased Nrf2 Expression In Patients After Neoadjuvant Chemotherapy Is Associated With Poor Survival and Chemoresistance Insupporting
confidence: 79%
“…"Nrf2 addiction" refers to hyperactivation of the Nrf2 pathway in lung cancer cells, which promotes the development of NSCLC and can also enhance chemoresistance (19,20). Emerging evidence has shown that targeting Nrf2 is a potential therapeutic strategy for overcoming cisplatin resistance (21). Intriguingly, Truong Do M revealed that metformin suppresses the expression of Nrf2 at the transcriptional level by inhibiting Sirtuin 1 (Sirt1) (22), while another study reported the opposite result, with metformin also upregulating Sirt1 expression for decreasing the acetylation of Nrf2 and preventing its nuclear distribution (23).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently found that metformin augmented the cytotoxic effect of cisplatin to NSCLC cells by promoting NRF2 degradation through a mechanism similar to that of HepG2 cells, which is done by inhibiting Raf-ERK [ 122 ]. When treating lung adenocarcinoma cells with metformin, Zhang et al found that NRF2 expression was also reduced through ERK1/2 and PI3K-AKT pathway inhibition by metformin [ 123 ]. Isocitrate dehydrogenase 1- (IDH1) mediated chemoresistance in endometrial cancer cells can be abated by metformin treatment, which inhibits the IDH1-induced NRF2 expression [ 124 ].…”
Section: Direct Effects and Underlying Mechanisms Of Metformin On Hepatocytes Or Malignant Cells That May Inhibit Nash-related Hccmentioning
confidence: 99%
“…Metformin reduces the risk of lung cancer during anti-diabetic treatment [166]. A recent study showed that metformin suppresses proliferation and induces apoptosis of the human lung carcinoma A549 cells through the inhibition of the Akt and ERK1/2 signaling pathways and activation of Nrf2 [167]. These studies indicate the potency of Nrf2 phosphorylation pathways as therapeutic targets for lung diseases.…”
Section: Compounds Targeting Nrf2 Phosphorylation Pathwaysmentioning
confidence: 88%